PENGARUH KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI DAN IMPLIKASINYA PADA KEPUASAN KERJA PEGAWAI SEKRETARIAT DPRK BIREUEN - Munzir, Munzir; Syahriani, Endang (LPPM-UNIKI, 2023)
secretariat, with the aim of observing communication activities, leadership style, employee motivation and employee job satisfaction descriptively. And with path analysis trying to prove and measure: the influence of communication aspects and leadership style on employee motivation, the implications for job satisfaction of employees of the Bireuen DPRK secretariat. The results of the analysis show: a). there is a direct and indirect effect of communication aspects between employees and superiors on employee motivation, namely 49.78%, b). there is a direct and indirect effect of leadership style on employee motivation of 78.89%, c). simultaneously there is a significant influence of communication factors and leadership style on employee motivation of 62.8%, d). there is an effect of motivation on employee job satisfaction of 87.0%, e). there is a direct and non-communicative effect on employee job satisfaction of 54.56%, f). there is a direct and indirect effect of leadership style on employee job satisfaction of 96.5%, and g). simultaneously there is a significant influence of communication and leadership style on job satisfaction of employees of the Bireuen District DPRK Secretariat of 53.3%.